2014
DOI: 10.2147/dddt.s56801
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel: new uses for an old drug

Abstract: Paclitaxel (Taxol), one of the most important anticancer drugs, has been used for therapy of different types of cancers. Mechanistically, paclitaxel arrests cell cycle and induces cell death by stabilizing microtubules and interfering with microtubule disassembly in cell division. Recently, it has been found that low-dose paclitaxel seems promising in treating non-cancer diseases, such as skin disorders, renal and hepatic fibrosis, inflammation, axon regeneration, limb salvage, and coronary artery restenosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(29 citation statements)
references
References 52 publications
0
24
0
5
Order By: Relevance
“…Pathological studies have indicated that VSMCs serve a key role in the development of PAH, and may therefore present a therapeutic target for PAH in the future. PTX is a commonly used anticancer drug with applications as chemotherapy drug in in breast cancer, ovarian cancer, head and neck cancer, esophageal cancer, lung cancer and others (26), applications in skin disorders, renal and hepatic fibrosis, inflammation, axon regeneration, limb salvage, and coronary artery restenosis (27). The effective therapeutic concentration of PTX ranges from 1 nmol/l to 100 µmol/l.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological studies have indicated that VSMCs serve a key role in the development of PAH, and may therefore present a therapeutic target for PAH in the future. PTX is a commonly used anticancer drug with applications as chemotherapy drug in in breast cancer, ovarian cancer, head and neck cancer, esophageal cancer, lung cancer and others (26), applications in skin disorders, renal and hepatic fibrosis, inflammation, axon regeneration, limb salvage, and coronary artery restenosis (27). The effective therapeutic concentration of PTX ranges from 1 nmol/l to 100 µmol/l.…”
Section: Discussionmentioning
confidence: 99%
“…Goodness-of-fit test of SR, OLSR, PCR and PLSR models was performed to detect the best model for predicting each output variables (DW, intracellular paclitaxel, extracellular paclitaxel, total yield of paclitaxel and extracellular paclitaxel portion). High VAF, R 2 and RPD values and low RMSE and MAPE values displayed the model capability.…”
Section: Regression Modelsmentioning
confidence: 94%
“…Paclitaxel is a well-known chemotherapeutic agent widely applied as a therapy for various types of cancers [1], and this is also used as a treatment for non-cancerous human diseases [2]. Paclitaxel as a cytoskeletal drug arrests the proliferation of tumor cells following stabilizing the microtubules.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is also used for the management of diseases such as head and neck cancers, smallcell and non-small-cell lung cancers (NSCLCs), and AIDS [36]. Apart from cancer, paclitaxel is also used in the treatment of coronary heart disease, inflammation, axon regeneration as well as degenerative brain diseases, renal and hepatic fibrosis [37]. Paclitaxel-bound liposomes were studied In vitro and In vivo and demonstrated to be effective in the treatment of pancreatic cancer [38].…”
Section: Resultsmentioning
confidence: 99%